Factors associated with anemia among pregnant and lactating women during the COVID-19 pandemic in the targeted municipalities of five selected provinces in Nepal: a cross-sectional study - Pratik Niraula; Atul Upadhyay; Sanjeev Kumar Karn; Roman Karki (BMC Public Health)
Abstract Background Anemia poses significant health risks, especially affecting women and children, leading to increased morbidity, mortality, and adverse birth outcomes. The COVID-19 pandemic has further exacerbated economic challenges and food insecurity, and weakened immune systems affecting vulnerable populations like pregnant, and lactating women, and children. This study aimed to assess factors associated with anemia among pregnant and lactating women (PLW) during the COVID-19 pandemic in the targeted municipalities of five provinces of Nepal. Methods A cross-sectional study was conducted from August, 2022−April 2023 among 844 PLW (mean age 26.8 ± 4.96 years) from five provinces of Nepal selected through cluster sampling. A semi-structured electronic questionnaire, a paper-based 24-hour dietary recall, and hemoglobin concentration in the blood were recorded. Bivariate and multivariate binary logistic regressions were used to estimate the crude odds ratios (cOR), and adjusted odds ratios (aOR) with 95% confidence intervals (CIs). Results The overall prevalence of anemia among the study population was 41.2%, with a mean hemoglobin concentration of 11.58 ± 1.59 g/dL. Approximately 12.8% of respondents reported a loss of income during the COVID-19 pandemic. In addition, 46.4% observed an increase in food prices, and 25.4% noted a decline in the availability of diverse and nutritious foods. While the consumption of cereals and legumes remained relatively stable, a considerable proportion of respondents reported a reduced intake of fruits, vegetables, milk, meat, and eggs. Multivariate analysis showed that women with no formal education (aOR = 3.251, 95% CI: 1.728–6.115) and those with low dietary diversity (aOR = 3.054, 95% CI: 2.248–4.15) had significantly higher odds of being anemic. Conclusions The high prevalence of anemia among PLW highlights a critical public health issue, exacerbated by the COVID-19 pandemic. The findings call for targeted interventions that improve women’s education and promote dietary diversity as key strategies to prevent anemia and enhance maternal nutrition during both emergency and recovery phases.